Characterization of emergency department visits in pediatric patients within first year of liver transplantation: ten years experience in tertiary care center - Reem Elmokattaf; Ahmad Aljumaa; Majd Alani; Jihad Aljumaa; Nayef Latta; Hossam Ali Basha; Ahmed Mohamed Elhassan; Ismail A. Abdullah; Mohammad Aljumaa; Saleh M. Al-Yahri; Farooq Pasha (BMC Emergency Medicine)
Abstract Background Liver transplantation is a complex procedure associated with significant post-operative challenges. Monitoring the frequency and timing of Emergency Department (ED) visits post-transplant in a vulnerable population like pediatrics can provide critical insights into patient outcomes and the effectiveness of post-operative care. Objective This study aims to evaluate the indications, frequency, reasons and length of stay for ED visits among liver transplant recipients within the first year following discharge post-transplantation. Methods A retrospective observational study was conducted on 361 liver transplant recipients, analyzing the frequency, timing, indications, reasons and length of stay for their ED visits post-discharge over 10 years. Results 361 patients were analyzed in this study with a total of 1300 emergency department visits. (52%) of the patients were males and (48%) were females. Most transplants were from living donors (93%, N = 338). Patients with at least one comorbidity accounted for 35% of total patients with hypertension 6% (20), congenital heart disease 5% (n = 18), and seizure disorder 4% (n = 15) representing the most common comorbidities. Most common indications for liver transplant were biliary atresia (21%) and progressive familiar intrahepatic cholestasis (20%). The most common reasons for ED visits were gastrointestinal symptoms (32%), pulmonary symptoms (22%), and infectious symptoms (16%). Patients’ average length of stay in the hospital was 4 ± 10.7 days. Visits within the first 6 months accounted for 58% of total visits in the first year with first and second visits accounting for 47% of total emergency department visits. Conclusion The study highlights the high frequency of emergency department visits in pediatric subgroup as well the first 6 months as a critical period for follow-up. The study also demonstrated the continuous representation to the emergency department which calls for a closer follow-up and interventions to prevent those revisits. Clinical trial number Not applicable.